Prevalence of Campylobacter species in human, animal and food of animal origin and their antimicrobial susceptibility in Ethiopia: a systematic review and meta-analysis - Tizazu Zenebe; Niguse Zegeye; Tadesse Eguale (BMC, 2020)
Abstract Background Campylobacter jejuni and Campylobacter coli accounts for most cases of human gastrointestinal infections. The infection occurs through ingestion of contaminated food or water, and direct contact with feces of infected animal or human. Regardless of few local reports of Campylobacter and its antimicrobial susceptibility profile, there is no comprehensive data that show the burden of Campylobacter infection at national level in Ethiopia. This systemic review and meta-analysis aimed to determine the pooled prevalence of Campylobacter and its resistance patterns in Ethiopia from different sources. Method A comprehensive literature search of PubMed, Google scholar, Science direct and Google engine search was conducted for studies published from 2000 to July 30, 2020 on prevalence and antimicrobial susceptibility of Campylobacter in human, animal and food. The study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Checklist. Data from articles was extracted using a standardized data extraction format. The quality of the studies was assessed based on the Newcastle-Ottawa scale. The Q test and I2 test statistic were used to test heterogeneity across studies. The Pooled estimate of prevalence of Campylobacter species and its antimicrobial susceptibility profile was computed by a random effects model using STATA 16.0 software. Results were presented in forest plot, tables, funnel plot and figures with 95% confidence interval. Results A total of 291 articles were retrieved initially. The pooled prevalence of Campylobacter species from different sources was 10.2% (95% CI 3.79, 16.51). In this meta-analysis, the lowest prevalence was 6.0% whereas the highest prevalence was 72.7%. In the sub-group analysis, the pooled prevalence was similar in Amhara and Oromia region, higher in Gambella and lower in Sidama. Prevalence of Campylobacter was higher in animals (14.6%) compared to humans (9%). The pooled antimicrobial resistance rates of Campylobacter species to different antimicrobials ranged from 2.9-100%. Overall, higher rate of resistance was to cephalothin (67.2%), gentamicin (67.2%), and trimethoprim-sulfamethoxazole (33.3%) in Campylobacter isolates from all sources. In isolates from human, resistance to cephalothin was 83% followed by amoxicillin (80%), amoxicillin-clavulnate (36%), trimethoprim-sulfamethpxazole (32%), clindamycin (31%) and ceftriaxone (28%). On the other hand, higher rate of resistance to penicillin (100%), cephalothin (60%), ciprofloxacin (71.2%), and trimethoprim-sulfamethoxazole (39%) was recorded in isolates from animals. Conclusion The present study highlights the burden of Campylobacter species in the country and higher rate of resistance among investigated isolates. Designing appropriate prevention strategies and further local in-depth studies are recommended to establish actual epidemiological burden of the bacteria in the country.